Legal analysis of the parties partnership agreement in the tiktok affiliate program - Vivi Sylvia Purborini (Trigin Publisher, 2023)
Human activities have begun to shift by relying on online buying and selling platforms to carry out their activities. One of the well-known platforms is Tiktok. Apart from providing space for sellers and buyers to transact, TikTok also provides an affiliate program for content creators who want to market products from TikTok sellers, and in return is to get a certain commission when the product being promoted is successfully sold. In the process of activities related to affiliation, problems can arise because the legal relationship between the parties is still unclear. Based on this description, the author examines the legality of agreements in the tiktok affiliate program. This study uses a type of normative research. The research approach used is a statutory and conceptual approach. The legal material search technique that the author uses is through library research. The agreement between the service providers, namely TikTok in the affiliate program, is a form of partner / partnership cooperation, and the agreement is carried out by default. The clauses in the terms and conditions of the affiliate program are standard clauses. therefore the terms and conditions of the tiktok affiliate program are compelling. Legal consequences if a violation occurs, namely the non-fulfillment of the conditions in the agreement clause that has been agreed upon by the parties in the tiktok affiliate can be null and void. The limitation of this journal review is that information about the basis for making decisions on the amount of commission received by content creators who are included in the affiliate program is still unclear as to the source and legal basis. There is also no legal umbrella that determines affiliate commissions in the form of legal regulations in Indonesia.